Expression of CD44 variant isoforms, CD44v3 and CD44v6, are associated with prognosis in nasopharyngeal carcinoma. Issue 9 (25th July 2016) - Sagawa, K; Uwa, N; Daimon, T; Sakagami, M; Tsujimura, T
Abstract: Objective: The clinical and prognostic significance of CD44 variant isoform expression in nasopharyngeal carcinoma is not well known. This study aimed to clarify whether CD44 variant isoform expression serves as a prognostic factor in nasopharyngeal carcinoma. Methods: Forty-two nasopharyngeal carcinoma patients, who underwent concurrent chemoradiotherapy as the initial treatment, were the subjects of investigation. Expression of CD44 variant isoforms, CD44v3, CD44v4, CD44v5, CD44v6 and CD44v7, in nasopharyngeal carcinoma was assessed in relation to concurrent chemoradiotherapy resistance and disease-specific survival of the patients. Results and conclusion: The patients with CD44v6 high expression showed a clinically incomplete response to concurrent chemoradiotherapy at the primary site. The disease-specific survival rate was lower in patients with high expression of CD44v3 than in those with low expression. These results suggest that analysis of CD44v6 and CD44v3 expression is useful in estimating prognosis and determining effective treatment strategies in nasopharyngeal carcinoma.